KEGIATAN KNOWLEDGE SHARING PADA KOMUNITAS THE LOCAL ENABLERS JATINANGOR - Ria Maudi Fatimah; Yunus Winoto; Dian Sinaga (Metakom, 2021)
This study aims to determine how the process of knowledge sharing activities in the community based on socialenterpreneurship based on referring to the theory of Nonaka and Takeuchi, SECI in Yusuf's book that explains the four knowledge converts including Socialization, Externalization, Combination, and Internalization. The method used is qualitative with a case study approach. Data collection techniques used through observation, interviews, and literature study. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study indicate that the knowledge sharing activities carried out in the community of The Local Enablers occur in formal and informal activities. Formal activities consist of Learning Day and Thursday sharing. Informal activities are activities without time limit through face to face or media such as Instagram and WhatsApp, these activities are carried out anytime and anywhere. The conclusion of this research is sharing activities in the context of sharing knowledge behind the same experience. There are responses and opinions from each member in response to topics discussed in formal and informal activities. Which then can produce writing and images in the form of documents, archives and others to be used again by community members. From these results the advice that can be given is the need for a planned management system. such as digital storage plus the need for networks to access must be able to pay attention to consumers, especially members for the smooth dissemination of information.